Indoor air quality in primary schools - Canha, Nuno (2013)
The indoor air quality (IAQ) in classrooms is expected to play a key role in the assessment of the effects of the children’s personal exposure to air pollution since they spend on average 7–11 h per weekday at school. A statistical treatment was conducted over a database of indoor air parameters and the primary schools where these parameters were sampled (urban area of Lisbon, Portugal). The aim of this study was to assess the associations between indoor air parameters with the schools’ building characteristics, through the use of statistical methods. Several associations were found and allow pointing out from this study several recommendations to improve the classrooms IAQ. For example, some factors such as ventilation, cleanings and chalk use instead whiteboard pens, can reduce or increase specific contaminants inside the classrooms.